2009
DOI: 10.1128/aem.00206-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofYersinia enterocoliticaat the Species and Subspecies Levels by Fourier Transform Infrared Spectroscopy

Abstract: intermedia, and Y. rohdei strains from Y. enterocolitica, which could not be differentiated by the API 20E test system. The probability for correct biotype identification of Y. enterocolitica isolates was 98.3% (41 externally validated strains). For correct serotype identification, the probability was 92.5% (42 externally validated strains). In addition, the presence or absence of the ail gene, one of the main pathogenicity markers, was demonstrated using FT-IR. The probability for correct identification of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 29 publications
2
61
0
3
Order By: Relevance
“…For this purpose, bacterial isolates were cultivated on sheep blood agar plates (Oxoid) at 37°C for 24 h. Sample preparation, FT-IR spectroscopy (using IFS 28/B spectrometer, BrukerOptics, Ettlingen, Germany) and data acquisition were performed as described previously (Kuhm et al, 2009). Analysis of data was carried out using OPUS Software (vers.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…For this purpose, bacterial isolates were cultivated on sheep blood agar plates (Oxoid) at 37°C for 24 h. Sample preparation, FT-IR spectroscopy (using IFS 28/B spectrometer, BrukerOptics, Ettlingen, Germany) and data acquisition were performed as described previously (Kuhm et al, 2009). Analysis of data was carried out using OPUS Software (vers.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Species FTIRS HCA, ANN, PCA, SIMCA [45,49,53,86,92] Stenotrophomonas maltophilia Species FTIRS PCA, ANN [45,55] Ralstonia pickettii Species FTIRS ANN [45] Achromobacter spp Species FTIRS ANN [45] Yersinia spp. Species FTIRS, FTIRS-ATR ANN, SIMCA, PCA, CVA [47,50,52] Yersinia enterocolitica Serotype FTIRS ANN [47] Biotype FTIRS ANN [47] Yersinia ruckeri Biotype FTIRS ANN [80] Oscillatoria limosa Species FTIRS-ATR PCA, ANN [48] Arthrospira platensis Species FTIRS-ATR PCA, ANN [48] Phormidium spp. Species FTIRS-ATR PCA, ANN [48] Scytonem javanicum Species FTIRS-ATR PCA, ANN [48] Nostoc punctiform Species FTIRS-ATR PCA, ANN [48] Salmonella spp.…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
“…However, one year later, Coutinho et al [46] showed that FTIRS could lead to a high rate of misidentifications of B. cepacia complex species. In 2009, Kuhm and collaborators [47] successfully discriminated 4 Yersinia species based on their IR spectra and ANN. In 2004, seven cyanobacterial strains belonging to five different genus and/or species were also successfully discriminate by FTIRS-ATR and ANN (Bounphanmy and co-workers [48] ).…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
See 2 more Smart Citations